Response of post-larva of snakehead (Channa striata) to feeding dried silkworm (Tubifex sp.) and artificial diet - Mas Bayu Syamsunarno; Mas Tri Djoko Sunarno (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
Post-larval snakehead (Channa striata) can be fed on live silkworms (Tubifex sp.), artificial feed and a combination of both as a source of nutrients. The availability of live silkworms depends on the yield in nature. Meanwhile, dried silkworms are available in the market. Therefore, the study to evaluate feeding combinations of dried silkworms and artificial feed for the rearing of post-larvae snakehead was conducted from October to December 2020 in Serang District, Indonesia. The treatments were combinations of dried silkworm and artificial feed at a ratio of 100:0%, 75:25%, 50:50%, 25:75%, and 0:100%, respectively. After being adapted to experimental conditions, post-larvae of snakehead (0.40±0.02 g) were randomly stocked in 15 happas of 50x70x75 cm in dimension size each at a rate of 25 post-larvae and fed on tested diet according to the treatments at 5% of biomass a day, divided into three times for 40 days of experimental periods. The post-larvae of snakehead performed the best growth at the contribution of dried silkworm at 100 – 25%, the best feed conversion and protein efficiency ratio at 100 – 50% and 50%, respectively and the best survival at 50 – 0%. It could be suggested that feeding dried silkworm and artificial feed at a 50:50 ratio, respectively, during post-larvae snakehead rearing.Keywords:Channa striata Feeding combination Nutrient sourcesPost-larvae rearing